TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH TERHADAP AKTA JUAL BELI YANG CACAT HUKUM (STUDI PUTUSAN PENGADILAN NEGERI JAKARTA TIMUR NOMOR 347/PDT.G/2017/PN.JKT.TIM) - Jessica Fionita; Hasni Hasni (Fakultas Hukum Universitas Tarumanagara, 2020)
The Deed of Sale is the deed made by the land deed official as evidence of a legal act of transfer of rights by way of buying and selling. Therefore, if the contents of the Deed of Sale contain legal defects, the transfer of rights can be said to be invalid. Then, what is the responsibility of the Land Deed Official for a legal defect in the Deed of Sale? The author in examining the problem using the normative method. The primary data that the author uses comes from interviews with those relating to the Land Deed Official, while secondary data comes from books that relate to the agrarian sector. Research suggests that the authority of the Land Deed Official was the making of an authentic deed related to agrarian/lands. Therefore, when legal defect exist in the Deed of Sale due to the mistake of the Land Deed Official, the Land Deed Official could be charged with administration sanction, civil sanction, and criminal sanction as a form of accountability. Thus, the responsibility for the Land Deed Official who erred in the making of Deed of Sale is administrative responsibility, civic responsibility, and criminal responsibility. It is good the be sure that before the Land Deed Official make the Deed of Sale, the Land Deed Official is consulted first about the data from Indonesian National Land Office.